Regulation of curd initiation in the summer cauliflower - Hand, David John (1988)
Factors regulating curd initiation in the summer cauliflower were examined with special attention given to responses to change in environment. Low temperature treatments of four weeks at 5°C accelerated curd initiation, reducing the number of leaves initiated before the curd. A reduction in vegetative growth was associated with earlier curd initiation. The extent of the low temperature effect was dependent on genotype, temperature, treatment duration and the plant's stage of development when low temperature treatments commenced. A distinct juvenile phase was observed when plants were incompetent to perceive chilling as a vernalization stimulus. Phase transition from the juvenile to the mature, competent form was associated with the initiation of a specific number of leaves. These were 14 and 18 leaves for cvs Perfection and White Fox respectively, leaf number being higher in the later season cultivar. The duration of phase change itself was short, lasting approximately two plastochrons. Increase in leaf initiation rate was associated with phase transition. Rate of leaf initiation increased with increasing temperature. Duration of the juvenile phase, measured chronologically, was therefore shorter at higher temperatures. Shoot dry weight was linearly related to leaf number in plants examined here; this characteristic would also be a stable marker for phase transition. Chilling imbibed seed proved ineffective in accelerating curd initiation. Reduction in total irradiance receipt delayed curd initiation in plants grown under warm conditions. Associated with this delay were reductions in rate of leaf initiation and stem dry weight increment. Photoperiods of 16 h following sub-optimal vernalization allowed faster curd initiation than photoperiods of 8 hand 24 h. A minimum stem dry weight at curd visibility was achieved under this regime. Reciprocal of leaf number subtending the curd, denoting the rate of progress towards curd initiation, was shown to be linearly related to temperature under controlled environment conditions. Curd initiation rate in . cv Perfection increased after treatment in the temperature range -1.2SoC to 5.5°C and decreased after treatment over the range 5.5°C to 23.5°C. Similarly, in cv White Fox, curd initiation rate increased following treatments at temperatures of -3.0°C to 8.6°C and declined over the range 8.6°C to 31.5°C. Linear regressions also adequately described the relationship of rate of curd appearance on temperature. Rate of curd appearance in cv Perfection increased following treatment at temperatures of -4.5°C to 12°C and declined over the range 12°C to 29.5°C. In cv White Fox rate of curd appearance was shown to increase following treatment over the range -3.5°C to 15.8°C and decline from 15.8°C to 28.3°C. The different cardinal temperatures from those established for curd initiation were probably the result of examining not one process but two: curd initiation and early curd growth. Their two distinct optimum temperatures would account for the observed parabolic trend. The relationship between leaf number subtending the curd and thermal time established under controlled environment conditions was extrapolated to predict curd initiation time in the field. Thermal times of vernalization for plants grown under field conditions showed close agreement with controlled environment figures at early transplantings, but not for late transplantings. This drift was probably due to irradiance receipt whereby increasing irradiance would partially SUbstitute for low temperature in accelerating curd initiation. Curd growth and morphology were clearly influenced by post-chilling temperature conditions. Linear functions adequately described regression of Loge curd diameter or curd weight on thermal time. Thermal requirement for a specified curd diameter could therefore be calculated. Increasing supply of mineral nitrogen accelerated curd initiation in unchilled plants. Curd initiation in chilled plants, however, was not affected by nitrogen applications. Increasing nitrogen increased both leaf area and dry weight. A minimum leaf dry weight below which curd initiation could not occur was indicated. Both larger module size for plant growth and increased nitrogen levels increased the number of leaves initiated during propagation. Increased nitrogen during propagation accelerated curd initiation in the field. Severe water stress also accelerated curd initiation and reduced leaf growth. Application of GA4+7 to unchilled plants accelerated curd initiation more. than applications of GAS. GA4+7 generally increased stem dry weight and decreased leaf dry weight. The hypothesis was proposed that GA4+7 accelerated curd initiation by redirecting assimilates to apical regions of the stem. Curd initiation under field conditions was also accelerated by GA4+7.